Timescales of polycyclic aromatic hydrocarbon and dust continuum emission from gas clouds compared to molecular gas cloud lifetimes in PHANGS-JWST galaxies - Kim, Jaeyeon; Chevance, Mélanie; Ramambason, Lise; Kreckel, Kathryn; Klessen, Ralf S.; Dale, Daniel A.; Leroy, Adam K.; Sandstrom, Karin; Chown, Ryan; Williams, Thomas G.; Sarbadhicary, Sumit K.; Belfiore, Francesco; et al. (The astrophysical journal, 2025)
Recent JWST mid-infrared (mid-IR) images, tracing polycyclic aromatic hydrocarbons (PAHs) and dust continuum emission, provide detailed views of the interstellar medium (ISM) in nearby galaxies. Leveraging PHANGS-JWST Cycle 1 and PHANGS-MUSE data, we measure the PAH and dust continuum emission lifetimes of gas clouds across 17 nearby star-forming galaxies by analyzing the relative spatial distributions of mid-IR (7.7-11.3 μm) and Hα emission at various scales. We find that the mid-IR emitting timescale of gas clouds in galactic disks (excluding centers) ranges from 10-30 Myr. After star formation is detected in Hα, mid-IR emission persists for 3-7 Myr during the stellar feedback phase, covering 70%-80% of the Hα emission. This significant overlap is due to intense radiation from star-forming regions, illuminating the surrounding PAHs and dust grains. In most galaxies, the mid-IR time-scale closely matches the molecular cloud lifetime measured with CO. Although mid-IR emission is complex, as influenced by ISM distribution, radiation, and abundances of dust and PAHs, the similarity between the two timescales suggests that once gas clouds form with compact mid-IR emission, they quickly provide sufficient shielding for stable CO formation. This is likely due to our focus on molecular gas-rich regions of galaxies with near-solar metallicity. Finally, we find that the mid-IR emitting timescale is longer in galaxies with well-defined H ii regions and less structured backgrounds, allowing photons to more efficiently heat the ambient ISM surrounding the H ii regions, rather than contributing to diffuse emission. This suggests that the shape of the ISM also influences mid-IR emission.